Determination of seismogenic structures and earthquake magnitud from seismites in the Acequion river, Precordillera Range, central-western Argentina - Perucca, L. P.; Bracco, A. I.; Moreiras, S. M. (Journal of Iberian Geology, 2009)
Evidences for paleoearthquake induced liquefaction features in the Central Western Argentina were determined in the Acequión river valley. Well-preserved liquefaction structures were found in a Holocene lake dammed by rock avalanches. At least five paleoearthquakes affected this region during the Pleistocene-Holocene according to the temporal sequence established for these seismic structures and the rock avalanches recognized in the Acequion river. The magnitude of these triggering paleoevents and probable seismic source are analysed and discussed, concluding that liquefaction features and rock avalanches should be generated by M>5 earthquakes related to the nearby Cerro Salinas Fault belonging to Precordillera Oriental fault system. These findings allow us to extend the record of moderate to high magnitude-earthquakes to the Pleistocene-Holocene.